ANALISIS KINERJA PERUSAHAAN BERDASARKAN LAPORAN ARUS KAS PADA PT INDOMOBIL SUKSES INTERNASIONAL TBK - Hardiyanto, Arief Tri; Bertus, Stefan Michael Benyamin (Universitas Pakuan, 2015)
This research discusses the role of the analysis of the cash flow statement as supporting the evaluation of company performance based on cash flow ratio, so that it can be seen in the companys ability to manage cash, either in operating activities, investing activities, and financing activities. The analysis is expected to be useful as a supporting device in the decision making process for users of financial statements for both internal and external parties. Based on the analysis of the cash flow pattern, it can be seen operating activities resulted in net cash the company is negative. Thus the financial condition of PT Indomobil Sukses Internasional Tbk is not good. Cash flows from investing activities yielded negative results, thus the financial condition of PT Indomobil Sukses Internasional Tbk is both a financing cash flow generating net amount of cash flow that is positive. The third explanation pattern of cash flow, it can be concluded that the financial condition of PT Indomobil Sukses Internasional Tbk generally in poor condition. Then, based on the analysis of the cash flow statement, author obtained information that the company has liquidity and solvency levels that are less good. The capital structure of the company has not been sufficiently effective and efficient.Â Keywords: Analysis of Cash Flow Statement